2022
DOI: 10.3390/ijms23168977
|View full text |Cite
|
Sign up to set email alerts
|

The Impairment of Cell Metabolism by Cardiovascular Toxicity of Doxorubicin Is Reversed by Bergamot Polyphenolic Fraction Treatment in Endothelial Cells

Abstract: The beneficial effects of bergamot polyphenolic fraction (BPF) on the mitochondrial bioenergetics of porcine aortic endothelial cells (pAECs) were verified under the cardiotoxic action of doxorubicin (DOX). The cell viability of pAECs treated for 24 h with different concentrations of DOX was reduced by 50%, but the negative effect of DOX was reversed in the presence of increasing doses of BPF (100 µg/mL and 200 µg/mL BPF). An analysis of the protective effect of BPF on the toxic action of DOX was also carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In fact, BPF inhibited the Ca 2 + -activated F 1 F O -ATPase, therefore counteracting the opening and size of the mPTP with a final protective effect on mitochondrial dysfunction [ 24 ]. In the same cell line, the authors demonstrated that BPF counteracted the toxic effect of doxorubicin on cell viability and mitochondrial function [ 29 ]. Based on this in vitro study, BPF, by restoring the correct metabolic cellular functions, can behave as a positive agent toward the cardiovascular disorders resulting from the toxic action of doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, BPF inhibited the Ca 2 + -activated F 1 F O -ATPase, therefore counteracting the opening and size of the mPTP with a final protective effect on mitochondrial dysfunction [ 24 ]. In the same cell line, the authors demonstrated that BPF counteracted the toxic effect of doxorubicin on cell viability and mitochondrial function [ 29 ]. Based on this in vitro study, BPF, by restoring the correct metabolic cellular functions, can behave as a positive agent toward the cardiovascular disorders resulting from the toxic action of doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoid profile analyzed by high-resolution mass spectrometry (Orbitrap spectrometer) and HRMSMS (ddMS2, data-dependent MS/MS) includes neoeriocitrin, naringin and neohesperidin. In addition, the entire HMG family is present with bruteridin and melitidin together with flavonoids such as 6.8-di-C-glycosides [ 24 , 28 , 29 ]. The BPF used in the present study was prepared and characterized by polyphenol content a month before performing the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Defective OXPHOS constituents or alteration of their functionality cause oxidative stress and, consequently, ROS imbalance. Antioxidants could scavenge excess ROS and reduce inflammatory responses by suppressing the inflammation phenomenon, renewing the mitochondrial bioenergetics under pathological or drug-induced imbalance conditions [ 61 ]. ROS-mediated oxidative modifications of biomolecules usually induces post-translational changes in proteins, i.e., phosphorylation, acetylation, ubiquitination, and SUMOylation, among others [ 62 ], or chemical modifications, through the oxidation of DNA bases.…”
Section: Mitochondria Are Potentially a New Target Of Natural Compoun...mentioning
confidence: 99%
“…Some different phytochemical compounds exploiting their antioxidant capacity have a scavenger action on ROS. As a consequence of decreasing ROS production, mitochondrial dysfunction is reduced, blocking the formation of PTP architecture and pore [ 78 ], and boosting the bioenergetic functionality of the mitochondrion [ 61 , 79 ]. On the balance, the antioxidant features of phytochemicals in terms of mitochondrial ROS production is translated into a cellular anti-inflammatory effect.…”
Section: Mitochondria Are Potentially a New Target Of Natural Compoun...mentioning
confidence: 99%
“…In plants, polyphenols—in addition to being involved in the maintenance of the organoleptic properties of plants and food—operate certain defensive strategies, thereby acting as protectors against multiple types of stress, including pathogens, oxygen and nitrogen species, parasites and plant predators, UV light, and oxygen and nitrogen species, among others. In contrast, the main properties exercised in humans include those of the antioxidative, anti-inflammatory, anti-cancer, and cardio-protective variety [ 190 , 191 , 192 , 193 , 194 , 195 , 196 ]. A successful strategy of administering polyphenols is to be found not only in the prevention/treatment of various pathologies, but also in the slowing of the progression of pathologies and in promoting the healing process [ 197 ].…”
Section: Nitrates–nitrites–nitric Oxide In Fruits and Vegetablesmentioning
confidence: 99%